Fairy-Tale TV - Rudy, Jill Terry, 1963-; Greenhill, Pauline (London ; New York : Routledge, 2020)
"This concise and accessible critical introduction examines the world of popular fairy-tale television, tracing how fairy tales and their social and cultural implications manifest within series, television events, anthologies, and episodes, and as freestanding motifs. Providing a model of televisual analysis, Rudy and Greenhill emphasize that fairy-tale longevity in general, and particularly on TV, results from malleability-morphing from extremely complex narratives to the simple quotation of a name (like Cinderella) or phrase (like "happily ever after")-as well as its perennial value as a form that is good to think with. The global reach and popularity of fairy tales is reflected in the book's selection of diverse examples from genres such as political, lifestyle, reality, and science fiction TV. With a select mediagraphy, discussion questions, and detailed bibliography for further study, this book is an ideal guide for students and scholars of television studies, popular culture, and media studies, as well as dedicated fairy-tale fans"--
Introduction: fairy-tale television (FTTV) invokes reality and possibility -- Historical perspectives and theoretical directions -- Event FTTV in musicals, movies and mini-series: exploring performance and transformation -- Anthologies: exploring community, fairy-tale happiness, and televisual storytelling -- Motif-spotting in advertising and reality: exploring lifestyle -- Episodes: exploring characters -- Series and seasons: exploring crime and justice in fairy-tale procedurals -- Conclusion: future excursions with FTTV wonder.
OCLC-licensed vendor bibliographic record.
Keywords: Fairy tales -- Television adaptations; Fairy tales on television; Plots (Drama, novel, etc.)